PENGGUNAAN GRAPH BASED METHOD DAN SOFTWARE BLOCPLAN UNTUK MEMPEROLEH LAYOUT YANG OPTIMAL DI DEPT. ACOUSTIC GUITAR PT. YMMI - Sulasmana Nur (Journal of Industrial and Engineering System, 2025)
YMMI is a manufacturing company engaged in the manufacture of acoustic and electric guitars. In the production flow, the average material handling distance in the Acoustic Guitar department (16,1m) is greater than that of Electric Guitar (12.7m), this causes a difference in the material handling cost of the Acoustic Guitar and Electric Guitar departments, where  the material handling cost  of the Acoustic Guitar department  is Rp. 495.334, and Electric Guitar amounting to Rp. 350.918. The distance shift, especially in the Top Coating – Finishing workstation with a distance of 44.6m and SR Top Coating – Finishing with a distance of 48.3m, makes the high cost  of material handling in the Acoustic Guitar department. The results of the Graph Based Method obtained the calculation of OMH/Day of Rp. 431.622, and the proposal of  Blocplan Software  of Rp. 373.085.  The minimum material movement distance was chosen, namely the Blocplan Software layout  proposal, with a percentage reduction in the total displacement distance of 20% calculated using the Rectilinear method calculation, as well as a reduction  in material handling costs  by 25%.